Meshless point interpolation formulation of kinematic wave equation for flood routing - Hirol, H. (Medwell Journals, 2017)
This study presents the meshless Point Interpolation Method (PIM) formulation to solve kinematic wave equation for flood routing. It details on Galerkin residual method employing PIM shape functions in discretizing the unsteady partial differential equation. Two nonlinear solvers are considered; Picard and Newton-Raphson. The formulation are verified against both hypothetical data obtained from conventional numerical methods (finite difference and finite element method) and gauged data obtained from an actual river. Close agreements are obtained between the proposed PIM formulation and the conventional methods thus highlight the potential of PIM as an alternative numerical method in the field of hydrologic modelling. © Medwell Journals, 2017.